EFEKTIVITAS BERAGAM METODOLOGI PEMBELAJARAN DALAM MENINGKATKAN HASIL BELAJAR SISWA: Metodologi Pendidikan - yani, Lili Epi Candra; Astuti, Mardiah; Anjani, Sri Mutia; Pramuja, Muhammad Derry; Pai E, Class (Jurnal Multidisipliner Kapalamada, 2025)
: This article examines the effectiveness of various learning methodologies in enhancing student learning outcomes through a comprehensive and multidimensional approach. The study analyzes diverse strategies including cooperative learning, problem-based learning, flipped classroom, inquiry-based learning, gamification, and the integration of digital technology and interactive multimedia. Each methodology is evaluated based on its advantages, implementation challenges, and impact on students’ cognitive, affective, and psychomotor domains. Findings indicate that the effectiveness of these methods is strongly influenced by contextual factors such as student characteristics, teacher readiness, school infrastructure, and the learning environment. Cooperative and problem-based learning significantly improve critical thinking and collaboration skills, while flipped classroom and gamification increase student motivation and deepen conceptual understanding through more personalized and adaptive learning experiences. The integration of digital technology broadens access to learning resources and enables personalized instruction tailored to individual student needs. However, optimal effectiveness is achieved only when the choice of methodology is flexible, taking into account class dynamics, learning objectives, and resource availability. Therefore, a diverse array of learning methodologies applied synergistically and adaptively can create an inclusive, innovative, and outcome-oriented learning environment that holistically improves student achievement.